2008
DOI: 10.2174/1874913500801010030
|View full text |Cite
|
Sign up to set email alerts
|

Foreign Language Competence in Content and Language Integrated Courses~!2008-03-28~!2008-05-27~!2008-06-11~!

Abstract: European educational systems are making great efforts to improve students' command of foreign languages, as there are many students who leave compulsory education with only the most limited ability to communicate in a foreign language. In this context the implementation of CLIL (Content and Language Integrated Learning) courses is becoming commonplace throughout Europe, because this approach is believed to significantly improve overall language competence in the target language. This paper examines the impleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

20
186
2
22

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 247 publications
(230 citation statements)
references
References 27 publications
(43 reference statements)
20
186
2
22
Order By: Relevance
“…For instance, the results as regards the effects of CLIL education on pupils' foreign language development and affective features have been extremely positive (e.g. Järvinen 1999;Lasagabaster 2008Lasagabaster , 2011Ruiz de Zabore 2008;Lorenzo, Casal and Moore 2009;Admiraal, Westhoff and de Bot 2006;Pihko 2007). The results of the effects of CLIL education on content learning have been slightly less consistent.…”
Section: Clilmentioning
confidence: 99%
“…For instance, the results as regards the effects of CLIL education on pupils' foreign language development and affective features have been extremely positive (e.g. Järvinen 1999;Lasagabaster 2008Lasagabaster , 2011Ruiz de Zabore 2008;Lorenzo, Casal and Moore 2009;Admiraal, Westhoff and de Bot 2006;Pihko 2007). The results of the effects of CLIL education on content learning have been slightly less consistent.…”
Section: Clilmentioning
confidence: 99%
“…Dalton-Puffer's findings, (2008). Ackerl (2007) and Lasagabaster (2008) demonstrated that students taught through the CLIL program possessed better writing preference than students who were not taught by CLIL. Lasagabaster (2008) emphasizes that CLIL is believed to be able to contribute positively to the preparation for international life, improve learning motivation, improve intercultural communication skills, improve implicit and incidental learning abilities and develop all language skills, especially writing skills.…”
Section: Why Clil?mentioning
confidence: 99%
“…The introduction of the content and language integrated learning approach (CLIL) in the countries of the European Union was bound to influence other language teaching contexts in the world (Lasagabaster, 2008;Lasagabaster & Sierra, 2010;Meyer, 2010). In the Far East, for example, English teachers in Japan, South Korea, Taiwan, and Hong Kong have conducted several studies to investigate CLIL and to compare its effectiveness to their traditional English as a Foreign Language (EFL) teaching methods (e.g., Yamano, 2013;Yang & Gosling, 2014;Yang, 2015).…”
Section: Introductionmentioning
confidence: 99%